Fraud Firms and the Matching Principle: Evidence from Korea - Hong, Jooyeon; Paek, Wonsun gamaijb@gmail.com (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
This paper examines whether the degree of matching for poor-performing fraud firms varies depending on the strength of the causal relation between expenses and revenues. A stronger causal relation exists between revenues and operating expenses than between revenues and total expenses that include non-operating expenses as well as operating expenses. Fraud firms have stronger incentives for managing earnings. Given that managing earnings is easier when using non-operating items than when using operating items, the degree of matching is (not) lower for fraud firms than for non-fraud firms at the strong (weak) level of the causal relation between revenues and expenses. Empirical results suggest that the degrees of matching are different between fraud and non-fraud firms only at the strong level of the causal relation between revenues and expenses. This result implies that the investigation of the matching model at a strong level of the causal relation between revenues and expenses is more effective than that at a weak level of the causal relation, with regard to examining the degree of matching for fraud firms. This study contributes to the literature by providing evidence on the importance of the level of the causal relation when examining the degree of matching.